Preparation of Pectin Membranes with Polyvinyl Alcohol (PVA) Blended Method as Dialysis Membrane for Urea Transport - Hastuti, Budi; Aurura, Garnish Teantine; Hadi, Saptono (Jurnal Kimia Valensi, 2025)
Pectin has shown the potential to act as membranes in a variety of applications, such as in biomedical applications such as that carried out in this study. This study aims to modify pectin with polyvinyl alcohol (PVA) for hemodialysis membrane applications. Pectin-PVA membranes were made by immersing the membrane with 4% PVA and tested for the membrane's filtration capacity for transport. Pectin-PVA membranes were tested using Tensile Test, Fourier Transform Infrared (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), and Thermal Test. The results showed that the pectin blended polyvinyl alcohol (PVA) membrane was successfully synthesized, confirmed by the spectra on FTIR there were OH vibrations, –CH2, –CH, -CO (ester) and CO (ether) bonds, PVA will increase the stress and strain value, XRD data shows that the membrane has a crystalline structure, SEM data shows that the membrane including in the microspheres, and the membrane undergoes carbonization at a temperature of around 400 °C there is an increase in the absorbance value, and the urea transport process increases the absorption of urea every hour.